Pengaruh Substitusi Tepung Beras Merah (Oryza nivara) dengan Penambahan Pisang (Musa paradisiaca l.) Terhadap Sifat Fisik dan Kimia Almond Crispy - Ageng Dwi Luthfi; Bareta Agdia Pury Artha (Food Scientia : Journal of Food Science and Technology, 2021)
Banana is a nutritious food and is a source of carbohydrates, vitamins and minerals. Brown rice is a food ingredient that is rich in anthocyanins. One of the simplest brown rice processing is the manufacturing of brown rice flour. The use and utilization of bananas andbrown rice flour as a substitute for food processing can be realized by industries engaged in the food sector, one of which is the bakery industry. This research purpose is to produce cookie products, namely almond crispy with banana and red rice flour substitution. The experimental design used is a completely randomized design with the first factor being the ratio of brown rice flour and bananas (80%: 20%; 70%: 30%; 60%: 40%). The secondfactor is the type of banana (Milk Banana, Ambon Banana, Kepok Banana). The results shows the highest water content is from the formulation of 60% brown rice flour and 40% Kepok Banana (3,74%), the highest ash level is from the formulation of 80% brown riceflour and 20% banana milk (3,85%) and the highest antioxidant activity is from theformulation with 70% brown rice flour and 30% banana milk (16,80%).